English language learning in response to the COVID-19 pandemic: Hong Kong English as a Second Language students’ perceptions of Badaboom! - Har, Frankie (Frontiers in Education, 2022)
In the midst of COVID-19 pandemic, many university courses delivered in English are conducted entirely online. However, if we continue using traditional teaching strategies and the same set of teaching materials, it would be extremely difficult for students, regardless of age, to focus in a two- or three-hour synchronous online class. As such, many researchers and educators are exploring different ways to engage students in today's digitally connected world. This article explores how English as a Second Language (ESL) undergraduate students cope up with emergency remote learning at The Hong Kong Polytechnic University during the COVID-19 pandemic. Using exploratory research design, one hundred university students from five English for Academic Purpose (EAP) classes who experienced blended learning using Badaboom!,a Game-based Student Response System (GSRS), for one semester were recruited to participate in the research. 30 students were interviewed to collect the data. The interview aimed to detail their responses so their strategies can be mapped clearly. The data reveal that the tertiary-level learners of this study feel that game-based classroom response system is useful for assisting them in overcoming ESL academic writing difficulties. The study reflects that, most students favour the interactivity and engagement afforded by Badaboom! due to the strong instructor-student and student-student interaction as well as students’ increased engagement.